Update on MRI Pulse Sequences for the Knee: Imaging of Cartilage, Meniscus, Tendon, and Hardware - Ariyachaipanich, Aticha; Bae, Won C.; Statum, Sheronda; Chung, Christine B. (Seminars in Musculoskeletal Radiology, 2017)
Magnetic resonance imaging (MRI) is widely used in the clinical setting as well as for research applications. Since its inception, technical development has broadly progressed as a response to challenges in both the clinical and research settings. Higher magnetic field strength and advances in hardware and software have revolutionized the diagnostic potential of MRI and moved well beyond diagnosis to characterization of tissue metabolism, biochemistry, disease pathogenesis, and material property, to name a few. This article focuses on state-of-the-art clinical and cutting-edge novel pulse sequences applied to knee MRI.
Keywords: quantitative MRI; UTE; T2; T1rho; osteoarthritis